PENINGKATAN KUALITAS SDM SISWA SMKN 2 SRAGEN MELALUI WORKSHOP ANIMASI 2D - Anung Rachman (Institut Seni Indonesia Surakarta, 2016)
In its development, animation cannot be separated from prehistoric era of hundreds to thousands years ago when the paintings of cave and temple ornaments have animation principles consisting orderly stack of paintings or ornaments. At this moment, animation has become part of the era of creative industry. People and the government seem to realize that it is time for animation in Indonesia to catch up remembering the great effect resulted from animation product. Along this time, many animation products from other countries come to the entertainment and advertisement business in Indonesia and we can do nothing for it. Consequently, people’s understanding towards local culture is getting faded and finally, more cultural assets are ‘stolen’ by other country. The culture ‘taking’, of course, is not absolutely the ‘taking’ country’s fault but it is also our fault for we don’t give response to the technological development that is able to make culture interesting. The workshop material is not only practice or introducing the making technique but also history, definition, application, and creating method.Key words : animation, history, culture, and local